Nanoscale direct-write fabrication of superconducting devices for application in quantum technologies. (1st March 2023) - De Teresa, José María
Abstract: In this Perspective article, we evaluate the current state of research on the use of focused electron and ion beams to directly fabricate nanoscale superconducting devices with application in quantum technologies. First, the article introduces the main superconducting devices and their fabrication by means of standard lithography techniques such as optical lithography and electron beam lithography. Then, focused ion beam patterning of superconductors through milling or irradiation is shown, as well as the growth of superconducting devices by means of focused electron and ion beam induced deposition. We suggest that the key benefits of these resist-free direct-growth techniques for quantum technologies include the ability to make electrical nanocontacts and circuit edit, fabrication of high-resolution superconducting resonators, creation of Josephson junctions and superconducting quantum interference device (SQUIDs) for on-tip sensors, patterning of high-Tc SQUIDs and other superconducting circuits, and the exploration of fluxtronics and topological superconductivity.